Employing Case Study Methodology in Special Educational Settings - Rouse, Angelise M. (Journal of the American Academy of Special Education Professionals, 2016)
In general, case studies are a preferred strategy when "how" or "why" questions are being posed, when the investigator has little control over events, and when the focus is on a contemporary phenomenon within some real-life context (Yin, 2009). This article will examine the advantages and disadvantages of employing case study methodology in special educational settings. The appropriateness of a case study design will be evaluated when designing a study regarding special education programming.